What do we know about no-show behavior? A systematic, interdisciplinary literature review - Caroline Amberger; Dominik Schreyer (Journal of Economic Surveys, 2022)
No-show behavior, a distinct form of absenteeism, is often problematic, particularly in the service industry. Given the growing relevance of the phenomenon in the industry, an increasing number of researchers from such different disciplines as educational economics, healthcare management research, and sports economics have begun examining both the potential antecedents and measures to counteract no-show behavior, recently. Although the continuously growing body of literature on no-show behavior has been reviewed before, most such previous attempts were neither interdisciplinary nor systematic, sometimes lacking both completeness and thoroughness. In this article, we address this gap in the still-emerging literature by providing a systematic, interdisciplinary review of the literature. We observe that, although the potential antecedents are manifold and not always neatly comparable across the different industries, there still exist commonalities, most of which are related to product characteristics and the opportunity costs arising from physical attendance. In contrast, although we document a promising effect of exploiting reminders in reducing no-show behavior, our understanding of the effectiveness of potential countermeasures is less pronounced.
Keywords: 330; absenteeism; appointments; attendance; non-attendance; no-shows; scheduling